Matematyka

Autorzy:Dubiecka-Kruk Barbara, Dubiecka Anna, Bazyluk Anna

Wydawnictwo:WSiP

Rok wydania:2014

Przekształć wyrażenie, korzystając ze wzoru na kwadrat sumy 4.43 gwiazdek na podstawie 7 opinii
  1. Gimnazjum
  2. 2 Klasa
  3. Matematyka

Przekształć wyrażenie, korzystając ze wzoru na kwadrat sumy

II
 Zadanie
III
 Zadanie
?
 Zadanie

A
 Zadanie

B
 Zadanie
C
 Zadanie
D
 Zadanie

`a)\ (n+5)^2=n^2+2*n*5+5^2=n^2+10n+25` 

`b) \ (3c+2)^2=(3c)^2+2*3c*2+2^2=9c^2+12c+4` 

`c)\ (5-x)^2=5^2-2*5*x+x^2=25-10x+x^2` 

`d)\ (2a-3c)^2=(2a)^2-2*2a*3c+(3c)^2=4a^2-12ac+9c^2`